REMEDIASI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI HUKUM NEWTON MENGGUNAKAN PENDEKATAN AUDITORY INTELLECTUALLY REPETITION - Dayu, Dayu; Djudin, Tomo; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aim of this research was to determine the effectiveness of students’ mistake in solving Newton law question of SMP Negeri 4 Teluk Keramat using Auditory Intellectually Repetition (AIR) approach for remediation. Design of research was pre-experimental with one group pretest-posttest. Data was collecting by using 5 essay question. The sample in this research was class VIII A. The sample was chosen by using intact group technic which done by giving pre-test to class VIII A-VIII D. There were 19 students’ for every class. Based on the result, the decrease of all student’s mistake was about 61,74%, there was mistake difference in solving questions significantly between before and after remediation ( and there was significant mistake difference observed by the term of mistake Based on effect size calculation was 0,66 (medium). Students’ mistake remediation in solving questions using AIR approach was expected to be used as on alternative for remediation activity to solve students’ mistake.Keywords: Remediation, mistake, Auditory Intellectually Repetition, Newton’s law